Educomunicação socioambiental nas rádios comunitárias da província de Gaza-Moçambique - Djive, Elias Gilberto Filimone (2022)
In this thesis, we aim to “Understand how the socio-environmental educommunication process takes place in community radios in the Province of Gaza-Mozambique”. With this aim, we are interested in studying how scientific knowledge and local knowledge are articulated in the communicational processes of environmental education, in the part of the country. To this end, our theoretical framework is diversified in a holistic way, but articulating itself from Freirean pedagogy and Kaplun's educational communication, from which the principles of: problematizing, dialogicity, criticality, participation and creativity with experimental aesthetics, in the communicational work of community radios. In this theoretical articulation, the Epistemologies of the South and Environmental Epistemology are included, through theorists such as Sousa Santos, Odera Oruka, Enrique Leff and Leonardo Boff. In the communicational field, community communication and educommunication are articulated, as counter-hegemonic alternatives of communicational processes, based mainly on Paiva, Peruzzo, Tomás Jane, and Soares. We take Socio-Environmental Educommunication as one of the areas of Educommunication, making a dialogue with the concept of Ecopedagogy, whose key authors are Gadotti, Ruskeinsky and Mazzarino. To conduct the empirical part, in the Province of Gaza, eight community radio stations were selected from that Province, which, through semi-structured interviews, analysis of programming schedules and radio programs on environmental education, reached the results of the study. The conclusions point to the existence of socio-environmental educommunicative practices in the studied radios, with greater focus on the principles of participation, problematizing, dialogicity, collaboration and creativity. However, deficiencies were found in the shared management model of the RCs, motivated by the low adherence of those in this management component. Finally, we conclude that the concepts of planetary citizenship and communicative citizenship are present and reciprocally in the studied radios, given that the collaborators, being mostly members of these communities, prioritize the interaction with other subjects who share the same community spaces, in the approach to environmental problems.